Angiomyofibroblastoma of the vulva: A rare case report with brief review of literature - Prita Pradhan; Nageswar Sahu; Kanakalata Dash; Pranati Misra; Urmila Senapati; Sudhanshu Kumar Rath (Wolters Kluwer Medknow Publications, 2019)
Angiomyofibroblastoma is an unusual tumor of pelvic and vulval region. It is often diagnosed in the middle-aged women. Although benign owing to its location and morphology, it has a few benign and malignant mimics. Here, we present such a case where a 42-year-old female presented with a vulval mass.